Placer - Simonín, Guy; Simonín, Guy; Bosc, Jacques; Bosc, Jacques; Nadeau, Marie; Nadeau, Marie (Ciencia y tecnología, 1998)
Muestra el origen y significado del placer, que es la emoción, tipos básicos.